Why Don’t We Center Abolition in Queer Criminology? - Walker, Allyn (Crime & delinquency, 2024)
In the last decade, queer criminology (QC) has emerged as a subfield of criminological research examining criminal-legal experiences of LGBTQIA+ individuals. Preceding and concurrent with this subfield, humanistic, and legal scholars outside criminology have worked to produce intersectional theorizations of queer, trans, and racial justice within and beyond the criminal legal system. However, numerous tenets of the latter literature have not been widely recognized by or integrated into QC scholarship. In this article, we consider how QC might more pointedly engage with this literature. We focus on how the concept of abolition has been mobilized in non-criminological theorizations of queer, trans, Black feminist, and racial justice, and how and why centering abolition in QC literature would positively shape QC’s legacy.